2012
DOI: 10.2310/jim.0b013e318250b101
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Mediated Left Ventricular Abnormalities in Chronic Kidney Disease

Abstract: Angiotensin II (ATII), the biologically active product of the renin-angiotensin system (RAS), is involved in modulation of left ventricular (LV) structure and function in chronic kidney disease (CKD). Because the RAS system is overactive in CKD, excess ATII accumulates in the heart, thereby promoting myocyte hypertrophy, fibroblast proliferation, interstitial accumulation of collagen, and microvessel disease. These cardiac abnormalities are further enhanced by a possible interaction between enhanced RAS activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 82 publications
1
15
0
1
Order By: Relevance
“…NE released by the sympathetic nerve endings may (1) directly induce proliferation of smooth muscle cell and adventitial fibroblasts in the vascular wall and exert a trophic influence on cardiac myocytes [57,58] or (2) indirectly evoke cardiac and vessel wall remodeling [59] via RAAS pathway activation and angiotensin II (Ang II) formation [60]. Studies also have demonstrated that cardiac sympathetic activity is related to LVH in patients with primary [61] or CKDmediated hypertension [62].…”
Section: Altered Autonomic Control Of Cardiovascular Function In Ckdmentioning
confidence: 96%
See 1 more Smart Citation
“…NE released by the sympathetic nerve endings may (1) directly induce proliferation of smooth muscle cell and adventitial fibroblasts in the vascular wall and exert a trophic influence on cardiac myocytes [57,58] or (2) indirectly evoke cardiac and vessel wall remodeling [59] via RAAS pathway activation and angiotensin II (Ang II) formation [60]. Studies also have demonstrated that cardiac sympathetic activity is related to LVH in patients with primary [61] or CKDmediated hypertension [62].…”
Section: Altered Autonomic Control Of Cardiovascular Function In Ckdmentioning
confidence: 96%
“…Factors increasing myocardial oxygen demand, including volume overload [105], sympathetic overstimulation [78,105], anemia [73,105], and hypertension [104], or trophic effects exerted by catecholamines [25, 45•], Ang II [59], and aldosterone [106,107,41] on cardiac myocytes have been implicated in the pathogenesis of cardiac damage in CKD, leading to fibroblast proliferation, interstitial accumulation of collagen, and microvessel disease [59]. Regarding reflex regulation of autonomic outflow, cardiac structural abnormalities also may influence reflex control of sympathetic and parasympathetic nerve activity, perhaps by interfering with the normal function of autonomic reflexes (e.g., the cardiopulmonary reflex) initiated at the level of the heart.…”
Section: Cardiovascular Remodeling In Ckdmentioning
confidence: 99%
“…According to these findings, they suggested that Ang II stimulates S100A12 production in macrophages [20]. Systemic and local activation of the renin-angiotensin system likely serves as a key pathogenic factor for complications associated with DM, CKD and CVD, and blocking Ang II production or action contributes to better outcomes of such diseases [21,22,23]. In this study, 62.5% of CKD patients were taking hypertensive agents, including ACEI or ARB, at the time of examination; however, there were no significant differences either in serum concentration or gene expression of S100A12 between the absence and presence of such drugs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms are predominantly regulated by the sympathetic nervous system and the renin-angiotensin system. Although dialysis patients generally have an overactive sympathetic nervous system and renin-angiotensin system [8,9,10,11,12], the increase in peripheral resistance is insufficient to prevent intradialytic hypotension in many patients [13,14]. As a consequence, the role of the vasoconstrictor arginine vasopressin (AVP) for maintaining blood pressure may become increasingly important [15,16,17].…”
Section: Introductionmentioning
confidence: 99%